Proceedings of the 19th International Conference on World Wide Web 2010
DOI: 10.1145/1772690.1772732
|View full text |Cite
|
Sign up to set email alerts
|

Equip tourists with knowledge mined from travelogues

Abstract: With the prosperity of tourism and Web 2.0 technologies, more and more people have willingness to share their travel experiences on the Web (e.g., weblogs, forums, or Web 2.0 communities). These so-called travelogues contain rich information, particularly including location-representative knowledge such as attractions (e.g., Golden Gate Bridge), styles (e.g., beach, history), and activities (e.g., diving, surfing). The location-representative information in travelogues can greatly facilitate other tourists' tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 19 publications
(20 reference statements)
0
72
0
Order By: Relevance
“…Unlike conventional studies that discover famous or popular POIs using a voting approach [2][3][4][5], because of the lack of related raw data on the Internet, our application discovers POIs that are not well known by analyzing information asymmetries among different user groups. This application well demonstrates the usefulness and novelty of the proposed models.…”
Section: Application Scenario: Discovering Obscure Poismentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike conventional studies that discover famous or popular POIs using a voting approach [2][3][4][5], because of the lack of related raw data on the Internet, our application discovers POIs that are not well known by analyzing information asymmetries among different user groups. This application well demonstrates the usefulness and novelty of the proposed models.…”
Section: Application Scenario: Discovering Obscure Poismentioning
confidence: 99%
“…Although obscure locations are less well known, they are often still worth visiting, and they are a valuable sightseeing resource for development and promotion. Recently, several studies [2][3][4][5] have shown the potential of UGC mining for discovering popular or famous locations and landmarks. Nevertheless, this area of research is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Yanai et al [64], [65] tried to detect cultural differences regarding certain world widespread concepts. Hao et al [66] presented a methodology for the automatic creation of travelogues, i.e., a kind of a travel-related experience logging. They retrieved geo-tagged photos from Flickr and embed them in these travelogues.…”
Section: Other Application Domainsmentioning
confidence: 99%
“…Hao et al [10] proposed a method for mining location-representative knowledge from travel blogs based on a probabilistic topic model (the Location-Topic model). Using this model, Figure 4.…”
Section: Recommending Tourist Spotsmentioning
confidence: 99%
“…They adopted the method of clustering blog photos relating to a particular tourist site, such as Louvre Museum in Paris. 10 Then they represented these photos as a graph based on the clustering results, and detected landmarks using link analysis methods, such as the PageRank [3] and HITS [19] algorithms.…”
Section: Recommending Landmarksmentioning
confidence: 99%